Predictive modeling of Alfvén eigenmode stability in inductive scenarios in JT-60SA - Coelho, R.; Vincenzi, P.; Vallar, M.; Rodrigues, P.; Tholerus, E.; Särkimäki, K.; Garcia, J.; Borba, D.; Nabais, F.; Calado, R.; Ferreira, J.; Figueiredo, A. (Frontiers in Physics, 2023)
The systematic analysis, over a large Fourier space of toroidal mode number/mode frequency, evidences that although the significant fraction of supra-alfvénic particles stemming from the negative ion source based neutral beam (500keV) can in some cases provide drive to AEs in both scenarios, it is not enough to overcome the thermal ion landau damping. In addition, the advanced scenario with ITB is shown to be also stable against AEs localised in the vicinity of the barrier, offering good prospects of sustainability of the plasma performance and of the ITB. Finally, some sensitivity scan results are shown on the influence of fast ion density and q-profile on the AE mode spectra and stability.2) Materials and Methods, 3) Results, 4) Discussion